2006
DOI: 10.1176/ajp.2006.163.4.623
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dissociative Disorders in Psychiatric Outpatients

Abstract: Dissociative disorders were highly prevalent in this clinical population and typically had not been previously diagnosed clinically. The high prevalence of dissociative disorders found in this study may be related to methodological factors (all patients were offered an interview rather than only those who had scored high on a screening self-report measure) and epidemiological factors (extremely high prevalence rates for childhood physical and sexual abuse were present in the overall study population).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
84
1
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(103 citation statements)
references
References 38 publications
6
84
1
7
Order By: Relevance
“…The proportion of 18.8% DD that we ascertained in our sample is comparable to previous findings in corresponding treatment settings in the US (Graves, 1989;Lussier et al, 1997;Foote et al, 2006) , Turkey (Sar et al, 2000), Finland (Lipsanen et al, 2004), and China (Xiao et al, 2006), thereby supporting the cross-cultural validity of DDs. All of our DD subjects had at least 1, and on average 3, comorbid axis I disorders.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The proportion of 18.8% DD that we ascertained in our sample is comparable to previous findings in corresponding treatment settings in the US (Graves, 1989;Lussier et al, 1997;Foote et al, 2006) , Turkey (Sar et al, 2000), Finland (Lipsanen et al, 2004), and China (Xiao et al, 2006), thereby supporting the cross-cultural validity of DDs. All of our DD subjects had at least 1, and on average 3, comorbid axis I disorders.…”
Section: Discussionsupporting
confidence: 89%
“…Despite their frequency of occurrence in psychiatric populations, the clinical relevance of DDs is unclear. In clinical practice, they are rarely diagnosed and rarely considered in treatment planning (Foote et al, 2006;Ginzburg et al, 2010). Some clinicians even question the diagnostic validity of certain types of DDs (Pope et al, 1999;Ginzburg et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Personality dissociation that develops to protect oneself from intense anxiety in the face of danger or intense stress can manifest itself in the form of dissociative amnesia, dissociative fugue, depersonalization, SW and ST [26]. Some authors report that Sleep-related aggressive behavior can be correlated with dissociative identity disorder in particular, dissociative fugue or dissociative disorder that cannot be named otherwise [8,20]. It is emphasized that the dissociative experiences during the daytime for those exposed to traumatic events can also occur at night and can be a cause of parasomnia [9,27].…”
Section: Discussionmentioning
confidence: 99%
“…Zadra et al were reported that NREM parasomnia episodes can be alpha, theta and delta wave or a combination of them without full awakening [31]. It was emphasized that, in PSG examination, hypersynchronous delta wave activity is seen at the beginning of NREM parasomnia episode [32], and that spectral wave power and slow delta waves were seen before the beginning of parasomnia episodes [8]. In our study, Group I had Sleep quality failure, delayed Sleep latency and Sleep Disorders, with subjective evalution of Sleep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation